PENGARUH HASIL PENGOMPOSAN SAMPAH ORGANIK MENGGUNAKAN MIKROORGANISME LOKAL (MOL) DAUN ANGSANA DAN BONGGOL PISANG - Firra Rosariawari; Laila Wahyu Susanti (EnviroUS, 2021)
ABSTRACT Organic Waste is object of this research. The research aims to study the process of making Mol from Angsana Leaves, Banana Roots/weevil and its applicate for composting process. The product of this research is from Organic waste, it’s used as bioactivator or local microorganism (Mol). This research was taken by many resources of article journal. Many product of Mol, consist of Angsana Leaves (Pterocarpus indicus) and Banana Roots are discussed. The result of composting by bioactivator each other are shown and observed. Fermentation from Angsana Leaves and Banana Roots is done for 15th day. The result research of composting process based on resource article journal revealed that : Angsana Leaves Mol meet the standard for pH, C-Organic, N-Total according SNI 19-7030-2004.